2008
DOI: 10.1111/j.1467-985x.2008.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Hitting and Missing Targets by Ambulance Services for Emergency Calls: Effects of Different Systems of Performance Measurement within the UK

Abstract: OnlineOpen: This article is available free online at www.blackwell-synergy.com Summary. Following devolution, differences developed between UK countries in systems of measuring performance against a common target that ambulance services ought to respond to 75% of calls for what may be immediately life threatening emergencies (category A calls) within 8 minutes. Only in England was this target integral to a ranking system of 'star rating', which inflicted reputational damage on services that failed to hit targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 82 publications
1
67
0
Order By: Relevance
“…Few other studies have looked at the impact of government-set time targets in healthcare and the majority of previous work has concentrated on examining the impact in terms of achievement of the target from a management perspective 6 9 17 18 20–23. All found that once a target was set, especially one accompanied by financial and/or punitive incentives, effort was expended to ensure it was met.…”
Section: Discussionmentioning
confidence: 99%
“…Few other studies have looked at the impact of government-set time targets in healthcare and the majority of previous work has concentrated on examining the impact in terms of achievement of the target from a management perspective 6 9 17 18 20–23. All found that once a target was set, especially one accompanied by financial and/or punitive incentives, effort was expended to ensure it was met.…”
Section: Discussionmentioning
confidence: 99%
“…Performance ratings in the NHS were seen as poor measures, which often neglected areas of excellence in poorly-rated organizations and pockets of failure in excellent institutions (Bevan and Hood, 2006). In the case of ambulance service, several unintended consequences of performance targets have been documented, some of which were the result of the underlying cultures in the ambulance service (Bevan and Hamblin, 2009;Wankhade, 2011).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Throughout, however, there has been especial emphasis on targets, in particular for the reduction of hospital waiting times and improved responsiveness of ambulance services (Bevan and Hamblin 2009;Connolly, Bevan, and Mays 2010). These policies involve severe penalties and attractive rewards for failure and success.…”
Section: Devolution and Health: The Emergence Of Policy Variationmentioning
confidence: 98%